1998
DOI: 10.1016/s1074-5521(98)90666-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating precursor-directed biosynthesis towards novel erythromycins through in vitro studies on a bimodular polyketide synthase

Abstract: Although a broad range of variation in the starter residue is acceptable, the substrate specificity of module 2 of a typical modular PKS in vitro is relatively intolerant of changes at C-2 and C-3. This will restrict the usefulness of approaches to synthesise novel erythromycins using synthetic diketides in vivo. The use of synthetic beta-keto diketides in vivo deserves to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…Biosynthetic studies with mini-PKSs such as DEBS 1-TE and DEBS 1 TE both in vivo and in vitro have yielded various structural and stereochemical analogues of lactones 2 and 3. 13,15,16,21,24,25 Analysis of these compounds by gas chromatography/mass spectrometry (GC/MS) has provided a powerful means of structural proof without the requirement for large quantities of analyte. With one exception, 16 however, these studies have not explored whether mass spectrometry can be used to probe the functionality or stereochemistry of these complex molecules.…”
mentioning
confidence: 99%
“…Biosynthetic studies with mini-PKSs such as DEBS 1-TE and DEBS 1 TE both in vivo and in vitro have yielded various structural and stereochemical analogues of lactones 2 and 3. 13,15,16,21,24,25 Analysis of these compounds by gas chromatography/mass spectrometry (GC/MS) has provided a powerful means of structural proof without the requirement for large quantities of analyte. With one exception, 16 however, these studies have not explored whether mass spectrometry can be used to probe the functionality or stereochemistry of these complex molecules.…”
mentioning
confidence: 99%
“…In vitro experiments comparing "natural diketide" and "propyl diketide" thioesters as substrates for purified DEBS have shown that the enzyme has a modest preference for the "propyl diketide" thioester over the "natural diketide" thioester (3,27). The "natural diketide"-thioglycolate and the "propyl diketide"-SNPC were first compared in the E. coli strain expressing DEBS1-mod2 and DEBS2 and -3 ( Table 4).…”
Section: Diketide Feeding With Alternatives To Snac Methyl S-[(2r‫3mentioning
confidence: 99%
“…However, production can be restored by addition of a synthetic thioester diketide that mimics the structure of the intermediate generated from the Wrst condensation cycle. The diketide enters the cell and can form the required thioester linkage with the second module of the PKS [3,11,27]. By varying the structure of the diketide employed, this process has opened up an avenue for production of a variety of novel analogues.…”
Section: Introductionmentioning
confidence: 99%